Photosynthesis-dependent Ca(2+) influx and functional diversity between phospholipases in the formation of cell polarity in migrating cells of red algae - Mikami, Koji (Landes Bioscience, 2009)
Unicellular spore cells, designated as monospores (also called archeospores), are well known as migrating plant cells, in which establishment of the anterior-posterior axis directs asymmetrical distribution of F-actin. Since the mechanisms of cell polarity formation are not yet fully elucidated in monospores, we investigated the roles of phosphoinositide signaling systems and Ca(2+) mobilization in migration. Although we have already found the critical involvement of phosphatidylinositol 3-kinase in the establishment of cell polarity, we recently demonstrated the important roles of extracellular Ca(2+) influx, phospholipase C (PLC) and phospholipase D (PLD). The remarkable characteristics of these factors are that Ca(2+) influx depends on photosynthetic activity and that PLC and PLD play roles in the establishment and maintenance of cell polarity, respectively. These findings could provide new insight into the regulation of migration in eukaryotic cells.